R1: Effects of Antihypertensive and Triglyceride‐lowering Agents on Hepatic Copper Concentrations in Rats with Fatty Liver Disease. (6th August 2014) - Ackerman, Zvi; Skarzinski, Galina; Grozovski, Maria; Oron‐Herman, Mor; Sela, Ben‐Ami
Abstract Copper deficiency had been suggested to link between fructose‐enriched diet (FED) and the development of non‐alcoholic fatty liver disease (NAFLD). In this study, we characterized changes in hepatic copper concentrations and hepatic oxidative milieu, in rats with the metabolic syndrome and NAFLD as a result of FED with pharmacological manipulations to reduce blood pressure or plasma triglycerides. Changes in plasma and hepatic copper concentrations were correlated with changes observed in the immunohistochemical hepatic expression of copper–zinc–superoxide dismutase (CuZnSOD; SOD1), metallothionein (MT) and nitrotyrosine (NITT). FED administration was associated with a 2.2‐fold reduction in hepatic copper concentrations, a decrease in the hepatic SOD1 expression, disappearance of the hepatic MT expression and increase in the hepatic NITT expression. Bezafibrate administration restored the hepatic copper concentrations and the hepatic SOD1 expression to levels that were observed in the control rats. A significant positive correlation between hepatic copper concentrations and the values of hepatic SOD1 expression of each animal included in this study was found. Administration of either captopril or bezafibrate increased hepatic MT expression, however, to levels that were lower than those observed in the control group. Administration of either amlodipine, or captopril or bezafibrate to the FED rats, had no effect on hepatic NITT expression. NAFLD development in FED rats is associated with a decrease in hepatic copper concentrations that is associated with a decrease in the hepatic SOD1 expression. Bezafibrate administration increases hepatic copper concentrations and restores the hepatic SOD1 expression.